PANDANGAN DUNIA KAUM MILENIAN DALAM NOVEL KERUMUNAN TERAKHIR KARYA OKKY MADASARI - dinda, Adinda; Taufik Dermawan (BASA Journal of Language & Literature, 2024)
The millennial generation is often considered a digital generation because it is easy to accept the times, namely technological developments that facilitate all activities. However, there are impacts that are influenced by technological developments. One of the novels that raised this phenomenon was the novel Kerumunan Terakhir. by Okky Madasari. Kerumunan Terakhir novel tells the story of man's stuttering of technological development. The purpose of this study is to describe perspectives from various parties on technological developments. The method used is descriptive-qualitative. With a sociological research approach and using Goldmann's genetic structuralism theory and the approach used is sociological. Data collection techniques include novels, recent crowds, and interviews with authors and millennials. Data analysis techniques in the form of data tricoagulation. The results of this study have three findings, first the structure of the novel text which forms two relationships, namely equal relations between characters and the power of characters and objects. Second, the millennial worldview of technological progress, that they think the presence of technology will have an impact on life, and the author's position as representing millennials in his work he gives advice in his novel. Based on this study which uses the novel Kerumunan Terakhir which discusses human stuttering towards technological developments. So it can be said from this novel that the presence of technology is able to affect all aspects of people's lives.